2011
DOI: 10.1111/j.1468-3083.2011.04021.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of melanoma: a population‐based study in a French regional population

Abstract: Information and screening campaigns should particularly target rural areas, males, older people and focus on nodular, acrolentiginous and unclassified subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
39
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 26 publications
10
39
1
1
Order By: Relevance
“…13·5% of the French population. This area has the highest density of cancer and/or melanoma registries in France, with four registries located in the regions of Alsace (Registre des Cancers du Haut‐Rhin, Registre des cancers du Bas‐Rhin), Franche‐Comté (Registre des Tumeurs du Doubs) and Champagne‐Ardenne (Observatoire du Melanoma en Champagne‐Ardenne) 14 …”
Section: Methodsmentioning
confidence: 99%
“…13·5% of the French population. This area has the highest density of cancer and/or melanoma registries in France, with four registries located in the regions of Alsace (Registre des Cancers du Haut‐Rhin, Registre des cancers du Bas‐Rhin), Franche‐Comté (Registre des Tumeurs du Doubs) and Champagne‐Ardenne (Observatoire du Melanoma en Champagne‐Ardenne) 14 …”
Section: Methodsmentioning
confidence: 99%
“…Champagne‐Ardenne). This region was chosen to enhance the feasibility of this pilot campaign, because it had previously been demonstrated that the proportion of thick melanomas was larger in this region than in the other five regions of north‐eastern France, and because a regional melanoma registry was available for evaluation …”
mentioning
confidence: 99%
“…Afin de s'approcher du seuil de 10 % de probabilité de trouver une mutation, défini par l'ASCO [1] et en tenant compte des données annuelles d'activité recueillies par l'INCa [48], sachant que l'âge moyen au diagnostic du méla-nome en France est d'environ 50 à 60 ans d'après le registre régional de Champagne-Ardenne [49], nous proposons que les contextes cliniques suivants justifient une prescription d'étude moléculaire des gènes du mélanome :…”
Section: Contexte Clinique Pour L'analyse Génétique Proposantunclassified